Estimation of stepwise crack propagation in ceramic laminates with strong interfaces - Náhlík, Luboš; Štegnerová, Kateřina; Hutař, Pavel (Gruppo Italiano Frattura, 2015)
The contribution deals with a description of the specific crack behaviour in the layered alumina-zirconia ceramic laminate. The main aim is to clarify crack behaviour in the compressive layer and provide computational tools for estimation of crack behaviour in the field of strong residual stresses. The crack propagation was investigated on the basis of linear elastic fracture mechanics.

The contribution deals with a description of the specific crack behaviour in the layered alumina-zirconia ceramic laminate. The main aim is to clarify crack behaviour in the compressive layer and provide computational tools for estimation of crack behaviour in the field of strong residual stresses. The crack propagation was investigated on the basis of linear elastic fracture mechanics.
Estimation of stepwise crack propagation in ceramic laminates with strong interfaces
Keywords: Ceramic laminates; crack behaviour; residual stresses; strain energy density factor; crack propagation direction.; Ceramic laminates; crack behaviour; residual stresses; strain energy density factor; crack propagation direction.